Chemical identification based on spectrogram - Adeebah, Jamar (2012)
Every chemical has its own element or composition. To determine the presence of this element, spectroscopic technique is used. Spectroscopic technique is a study interaction between matter/chemical with electromagnetic radiation (emr). Each chemical compound will have difference absorbance emr spectrum. In this project, the focus will be on Infrared region. In Infrared region, the functional group presence will be found. Chemical sample that have been use is polyethylene. Polyethylene will be undergoing degradation process with Manganese Laureate. Yield solution of the process will analyze by FTIR and the image of spectrogram will be recorded. In field of Electrical and Electronics Engineering field, the presence of functional group is determined based on image of spectrogram. As conclusion, hope this project will give impact to chemist to make analysis of chemical.